Proinflammatory cytokine (TNFalpha/IL-1alpha) induction of human osteoclast formation. - Kudo, O; Fujikawa, Y; Itonaga, I; Sabokbar, A; Torisu, T; Athanasou, N (2002)
TNFalpha and IL-1alpha are potent stimulators of bone resorption in vivo and in vitro. Recently, it has been demonstrated that these two cytokines directly induce osteoclastogenesis in mouse marrow cultures. This study determined whether TNFalpha (+/- IL-1alpha) is also capable of inducing human osteoclastogenesis. The CD14(+) monocyte fraction of human peripheral mononuclear cells was cultured with TNFalpha +/- IL-1alpha in the presence of M-CSF. TNFalpha induced the formation of multinucleated cells (MNCs) which were positive for TRAP, VNR and cathepsin K and showed evidence of resorption pit formation. IL-1alpha stimulated TNFalpha-induced lacunar resorption two- to four-fold. Osteoprotegerin, the decoy receptor for RANKL, did not inhibit this process. Anti-human IL-1alpha neutralizing antibodies significantly inhibited resorption without inhibiting the formation of TRAP(+)/VNR(+) MNCs. These results suggest that, in the presence of M-CSF, TNFalpha is sufficient for inducing human osteoclast differentiation from circulating precursors by a process which is distinct from the RANK/RANKL signalling pathway.